Peran TBM Bilik Urang dalam Pembelajaran Literasi Dasar Anak Pra Sekolah - Mahira Mujahida Ani Mufti; Anita Anita; Evi Afiati (UIN Sultan Maulana Hasanuddin Banten, 2022)
As a provision during the school period, it is important to introduce literacy to pre-school children. Community Reading Park (TBM) is one of the facilities that facilitate pre-school children in recognizing literacy. In this regard, it is important to explore how TBM introduces literacy to pre-school children. For this reason, this study discusses the role of the Bilik Urang community reading garden in introducing basic literacy to early childhood children in Cigadung Village, the majority of whom have low incomes. This study used a qualitative approach where data collection techniques were carried out through interviews, observations, and literature reviews. This study aims to describe the role of TBM Bilik Urang in introducing basic literacy to pre-school children and how volunteers manage the Bilik Urang Community Reading Park and implement basic literacy teaching strategies. The results of this study indicate that 1) the existence of TBM Bilik Urang helps introduce literacy to pre-school children, especially those from low-income families, 2) TBM Bilik Urang volunteers have a role in introducing literacy to children through planned strategies and activities. Keywords: Community Reading Park; basic literacy; early childhood ReferencesAffrida, E. N. (2018). Model Pembelajaran Literasi Dasar Dalam Mengembangkan Kemampuan Kognitif Dan Bahasa Di Taman Kanak-Kanak. Wahana, 70(2), 7–10. https://doi.org/10.36456/wahana.v70i2.1736Carol, S., & A. Wasik, B. (2008). Pendidikan Anak Usia Dini : Menyiapkan Anak Usia Tiga, Empat, dan Lima Tahun Masuk Sekolah (2nd ed., Vol. 1). Pearson Education. Darnis, S. (2020). The Development Of Children’s Story Book Media Based On Oral Story Of Local Tradition To Support The Literacy Program For Kindergarten Level. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(2). Dewayani, Sofie. (2019). Model Pembelajaran Literasi Untuk Jenjang Prabaca Dan Pembaca Dini (1st ed.) [E-book]. Badan Pengembangan Bahasa dan Perbukuan Kementerian Pendidikan dan Kebudayaan. Gibson, S. (2008). Reading aloud: A useful learning tool? ELT Journal, 62(1), 29–36. https://doi.org/10.1093/elt/ccm075Imroatun, I. (2018). Alternatif Media Pengembangan Literasi Baca Tulis Berbahasa Nasional bagi Siswa Raudlatul Athfal AH-. Al Hikmah Proceedings on Islamic Early Childhood Education, 1(April), 103–112. Kartini, Darmiyanti A, Riana N. Metode mendongeng kisah nabi dalam penanaman moral anak usia dini. As-Sibyan J Pendidik Anak Usia Dini. 2021;7(1):13-28. Kurniawan, H. (2018). Pengembangan Lingkungan Belajar Literasi Untuk Anak Usia Dini. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(1), 45–56. Lane, H. B., & Wright, T. L. (2007). Maximizing the Effectiveness of Reading Aloud. The Reading Teacher, 60(7), 668–675. https://doi.org/10.1598/rt.60.7.7Makin, L., & Whitehead, M. R. (2003). How to Develop Children′s Early Literacy: A Guide for Professional Carers and Educators (First ed.). SAGE Publications Ltd. Nurhayati, R. (2019). Membangun Budaya Literasi Anak Usia Dini dalam Keluarga. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 79–88. https://doi.org/10.47200/JNAJPM.V4I1.918Refiani, D. A., Umayah, & Mu’awwanah, U. (2019). Upaya Meningkatkan Kemampuan Mengenal Huruf Melalui Balok Huruf. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 4(2), 103–118. Rida Fironika K. (2005). Pembiayaan Pendidikan Di Indonesia. J Ilmu Pendidik Dasar. Published online:43-64. Saepudin, E., Agustini Damayani, N., & Sukaesih, -. (2017). Literasi Media Bagi Guru Paud Di Kecamatan Cicalengka. Dharmakarya, 5(1), 38–43. https://doi.org/10.24198/dharmakarya.v5i1.9892Saepudin, E., Sukaesih, S., & Rusmana, A. (2017). Peran Taman Bacaan Masyarakat (TBM) Bagi Anak-Anak Usia Dini. Jurnal Kajian Informasi Dan Perpustakaan, 5(1), 1. https://doi.org/10.24198/jkip.v5i1.10821Santoso, B., & Yusri, S. (2010). Skema dan Mekanisme Pelatihan (1st ed.). Yayasan Terumbu Karang Indonesia. Stewart, R. A., Bailey-White, S., Shaw, S., Compton, E., & Ghoting, S. (2014). Enhanced Storytimes: Effects on Parent/Caregiver Knowledge, Motivation, and Behaviors. Children and Libraries, 12(2), 9. https://doi.org/10.5860/cal.12n2.09Sumitra, A., & Sumini, N. (2019). Peran Guru Dalam Mengembangkan Kemampuan Minat Baca Anak Usia Dini Melalui Metode Read Aloud. Jurnal Ilmiah Potensia, 4(2), 115–120. https://doi.org/10.33369/jip.4.2.115-120Trelease, J. (2013). The Read-Aloud Handbook: Seventh Edition (7th ed.) [E-book]. Penguin Books. Widodo, M. M., & Ruhaena, L. (2018). Lingkungan Literasi Di Rumah Pada Anak Pra Sekolah. Indigenous: Jurnal Ilmiah Psikologi, 3(1), 1–7. https://doi.org/10.23917/indigenous.v3i1.3059Wijoyo H, & Indrawan I. (2020). Pendidikan Anak Pra Sekolah. Purwokerto: CV. Pena Persada.